The history of sketch comedy : a journey through the art and craft of humor - Key, Keegan-Michael, 1971-; Key, Elle (Chronicle Books LLC, 2023)
"The History of Sketch Comedy will appeal to all kinds of comedy fans as well as fans of Keegan-Michael Key. With epic personal tangents and hilarious asides, their story takes you on an illuminating look at all facets of comedy from the stock characters of commedia del arte in the 16th century, to the rise of vaudeville and burlesque, the golden age of television comedy, the influence of the most well-known comedy schools, and ascension of comedy films and TV specials--all the way through to a look at the future of sketch on social media platforms. Part masterclass, part memoir, and hilariously embellished with priceless commentary, The History of Sketch Comedy illuminates the essential building blocks of sketch comedy while interweaving Key's experiences of personal discovery and influence of his comedy heroes. The text is complemented by original art by Elle Key and exclusive essays compiled from conversations with some of their famous comedy friends and performers who have influenced the development of comedy, such as Jordan Peele, Mel Brooks, Julia Louis-Dreyfus, Mike Myers, Chris Rock, John Oliver, Tracy Morgan, Carol Burnett, Jim Carrey, and more"--